Teenage Pregnancy in India: Addressing Ethical Dilemmas - Jasti, Pratima; Behera , Surama Manjari; Behera, Priyamadhaba (Indian Journal of Community Health, 2024)
Teenage pregnancy remains a significant public health and social concern in India. This article examines the prevalence, contributing factors, and consequences of teenage pregnancy in India and explores the important ethical dilemma associated in context of pregnancy care in public health program and teenage pregnancy. Key factors for the teenage pregnancy include early marriage, lack of education, poverty, limited contraceptive use, and cultural norms. Teenage pregnancies are associated with higher maternal and infant mortality, pregnancy complications, and poor socioeconomic outcomes. While national programs address maternal health broadly, there is a lack of targeted interventions for teenage pregnancies, creating an ethical dilemma where this vulnerable group is left exposed to adverse events and outcomes. Additionally, teenagers under 18 are often excluded from key support programs, like conditional cash transfers, leaving them without essential resources. This article highlights the need for comprehensive strategies, including improved adolescent sexual education, behavior change communication, and specific support programs for pregnant teenagers. Addressing teenage pregnancy requires a multifaceted approach targeting social determinants, healthcare access, and cultural attitudes.